Epithelial dysregulation in obese severe asthmatics with gastro-oesophageal reflux. Issue 6 (27th June 2019) - Perotin, Jeanne-Marie; Schofield, James P.R.; Wilson, Susan J.; Ward, Jonathan; Brandsma, Joost; Strazzeri, Fabio; Bansal, Aruna; Yang, Xian; Rowe, Anthony; Corfield, Julie; Lutter, Rene; Shaw, Dominick E.; et al.
Gastro-oesophageal reflux disease (GORD) and obesity are associated with frequent exacerbations and poor quality of life in people living with asthma. Multiple mechanisms have been proposed for the effect of obesity, including modification of inflammation affecting epithelial cell proliferation and wound repair, while the role of GORD is poorly understood and proton pump inhibitors (PPIs) are of variable efficacy. GORD might exert a deleterious effect by inducing vagal reflex, neuroinflammation and directly triggering airway inflammation ( via microaspiration). Studies of reflux in animal models and human bronchial epithelial cell culture show varying impact on inflammation and airway remodelling. We have recently demonstrated changes in the sputum proteome in severe asthmatics with GORD, providing supportive evidence for gastric secretions exerting a direct effect on the airways [1]. The epithelium plays a key role in asthma, so in this study, we speculated that severe asthma in obese patients with GORD would be associated with epithelial dysfunction. Because GORD is treated with PPIs, drugs associated with risk of pneumonia and exacerbations of chronic obstructive pulmonary disease (COPD) and cystic fibrosis, the impact of PPIs was also assessed. Stratification of severe asthma on the basis of bronchial epithelial gene expression identified a subset whose endotype is defined by marked epithelial dysregulation associated with obesity, gastro-oesophageal reflux and proton pump inhibitors http://bit.ly/2EeKv23